HUBUNGAN PENGETAHUAN DENGAN KESIAPAN IBU DALAM MENGHADAPI MENOPAUSE DI POSYANDU KENANGA PUSKESMAS AIR SUGIHAN JALUR 25 - Bela Purnama Dewi; Yora Nopriani Yora Nopriani; italia italia; Nuning Sutarti Rimbawati Nuning Sutarti Rimbawati (LPPM STIKes Mitra Adiguna, 2023)
During this time many mothers realize that they will face menopause. But there are also mothers who are not ready to face menopause even though they are already aging. Many mothers who are not ready to face menopause need information to increase their knowledge about menopause. The information needed is adequate knowledge about various menopause problems and their solutions. The aim of this study was to determine the relationship between knowledge and mother's readiness to face menopause at Posyandu Kenanga Puskesmas Air Sugihan Jalan 25. The method used in this study uses correlation analysis with a cross sectional approach. The number of samples used was 43 respondents using a total sampling research technique. The results of the Fisher's Exact Test obtained a ρ value of 0.000 less than 0.05, so it can be concluded that there is a significant relationship between knowledge and mother's readiness to face menopause at Posyandu Kenanga Puskesmas Air Sugihan Jalan 25. The advice given is to provide counseling for mothers who are facing premenopause so that mothers are better prepared to face menopause.